Global acceptance and hesitancy of COVID-19 vaccination: A narrative review - Wardah Hassan; Syeda K. Kazmi; Muhammad J. Tahir; Irfan Ullah; Hibban Ar Royan; Marhami Fahriani; Firzan Nainu; Sandro GV. Rosa (Narra Sains Indonesia, 2021)
The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a major global health threat to human civilization and has disrupted many aspects of the community around the globe. Vaccination is one of the prominent measures to control the COVID-19 pandemic. More than 120 vaccines have entered human clinical trials and at least 8 vaccines have been fully approved. However, the success of the COVID-19 vaccination programs depends on how the community accepts the vaccines. Despite COVID-19 vaccination having been initiated for a while now, more than 50% of the global population have not been vaccinated. In some low- and middle-income countries (LMICs), the vaccine coverage is less than 20%. Since the decision to accept the new vaccine is complex, understanding the factors underpinning vaccine acceptance is critical. This review aimed to summarize the COVID-19 vaccine acceptance rate around the globe as well as its associated determinants. Information from this study might be important to formulate effective strategies to increase the COVID-19 vaccine coverage, and to be able to achieve herd immunity.